2019
DOI: 10.31686/ijier.vol7.iss1.1280
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Overcome Diversity Challenges between Urban/Rural Students in Universities

Abstract: The urban-rural imbalance between university students raises diversity challenges in many educational institutions. University leaders favor urban students’ admission because of the misconception that rural students have lower academic performance than their urban counterparts. Here, strategies to overcome diversity challenges between urban and rural students in universities have been proposed. A diversification workshop project was suggested to be delivered for the current and/or incoming students at KAU in R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
(4 reference statements)
0
5
0
Order By: Relevance
“…Students who enter university from rural backgrounds have unique experiences compared to their counterparts from the urban parts of the country (Maddah, 2019). In the case of Lesotho, it becomes clear that rural students also face numerous challenges in their transition into higher education, mainly due to the rural-urban imbalances that characterise this country.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
See 4 more Smart Citations
“…Students who enter university from rural backgrounds have unique experiences compared to their counterparts from the urban parts of the country (Maddah, 2019). In the case of Lesotho, it becomes clear that rural students also face numerous challenges in their transition into higher education, mainly due to the rural-urban imbalances that characterise this country.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…Their description turned out to be congruent with the conceptualisation of rurality adopted in this paper provided in the literature section. For instance, they indicated that rurality means, among others, a geographic area that is located away from the cities or towns, where only a few services are available (Leibowitz, 2017;Maddah, 2019). For some, rurality means a purely traditional area, with traditional ways of living and doing things.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
See 3 more Smart Citations